Conciliatory Justice in Modern Russia - DREMOVA, Katerina (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
The research studies conciliatory justice in modern Russia. Its formation and peculiarities in the institution of alternative ways of resolving legal conflict on the example of mediation are considered. Various views regarding the mediation definition are analyzed, and the author's vision of this category concept is given. The origins of mediation history abroad and in Russia are studied. The essence and peculiarities of mediation application as an alternative method of economic disputes settlement are characterized. The benefits of using conciliatory procedures in a business environment are revealed. The main aspects of the procedural legislation reform initiated by the Supreme Court of the Russian Federation concerning the change in the legal regulation of conciliatory procedures application in the settlement of legal conflicts are outlined. It is noted that the beginning of procedural reform in Russia with regard to dispute settlement through conciliatory procedures was triggered by the resolution of the plenum of the Supreme Court of the Russian Federation ‘On submission to the State Duma of the Federal Assembly of Russian Federation a federal law draft ‘On amendments to a number of legislative acts of the Russian Federation in connection with conciliatory procedure improvements’ adopted on 18 January 2018 and the resolution of the Government of the Russian Federation. Statistics on the ratio of dismissals agreed, dispute settlement through the mediation procedure, as well as plaintiff-triggered dismissals are provided. Methodology: the study is carried out on the basis of the universal method on scientific study of the social development principles –dialectical materialism provisions, as well as general and specific scientific methods: dogmatic, regulatory legal, legal comparative, fragmented historical and legal, case studies (statistical data and judicial statistics analysis), logical (hypotheses, analogy, modeling, analysis and synthesis methods), philosophic (axiological, derivation methods on the basis of priori and axiomatic provisions), generalization and abstraction methods. Conclusions: To date, entrepreneurs are increasingly using conciliatory procedures when settling disputes. This way of dispute settlement becomes very convenient, businessmen are not in the need to spend their time on litigation, often protracted, but can settle issues more quickly and effectively. Today, conciliatory justice in the Russian Federation is going through the stage of formation and development and in the future is to become a demanded institution of judicial law.